2022
DOI: 10.33225/pec/22.80.195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Distance Education Process in Sports Higher Education

Abstract: In present conditions, where distance education applications in higher education have become widespread due to the Covid-19 pandemic, it is seen in the research studies that the satisfaction levels of the lecturers and students are low. Although the developments in information technologies have reached advanced dimensions, the problems experienced in distance education systems have negatively affected the course functioning of the educators and the students' level of participation in the course. The issues exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(18 reference statements)
1
3
0
3
Order By: Relevance
“…Researchers emphasise that it may be useful to further develop how to approach quality issues (Miyazoe, 2008). Ozer (2022) conducted a study to evaluate the distance education process in sports sciences. The researcher claims that distance education is an alternative model that can be used in cases where the formal education system is disrupted for any reason.…”
Section: International Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers emphasise that it may be useful to further develop how to approach quality issues (Miyazoe, 2008). Ozer (2022) conducted a study to evaluate the distance education process in sports sciences. The researcher claims that distance education is an alternative model that can be used in cases where the formal education system is disrupted for any reason.…”
Section: International Contextmentioning
confidence: 99%
“…The researcher claims that distance education is an alternative model that can be used in cases where the formal education system is disrupted for any reason. Researchers agree that distance education applied during the COVID-19 process has positives and negatives for lecturers and students (Lamanauskas & Makarskaitė-Petkevičienė, 2021a;Ozer, 2022). A study conducted in Portugal showed that there is a relationship between how students perceive the pandemic as affecting their studies and their satisfaction with online course formats.…”
Section: International Contextmentioning
confidence: 99%
“…До переваг онлайн-навчання можна віднести розширений доступ здобувачів освіти до навчального контенту, зручна форма організації занять для викладачів та стандартизація навчального матеріалу в умовах використання LMS систем у процесі організації електронного формату навчання. Є також дані, що демонструють підвищену мотивацію здобувачів освіти до онлайн-навчання [9] та покращення результативності освітнього процесу [8].…”
unclassified
“…Дослідники сходяться на думці, що основним очевидним недоліком є здатність суто дистанційного формату фізичної підготовки сприяти розвитку рухових здібностей та контролювати фізичну активність тих, хто займаються [9]. Проте в жодному дослідженні не оцінювалася ефективність онлайн та змішаного формату навчання з погляду позитивного чи негативного впливу на розвиток рухових здібностей тих, хто навчаються, чи підвищення фізичної активності у вільний час.…”
unclassified
See 1 more Smart Citation